From Enoch to Tobit collected studies in ancient Jewish literature - Dimant, Devorah 1939- (Tübingen Mohr Siebeck, 2017)
Die in diesem Band versammelten Studien von Devorah Dimant untersuchen und analysieren jüdische Werke, die zur Zeit des Zweiten Tempels auf Hebräisch, Aramäisch oder Griechisch verfasst wurden, und erörtern deren Inhalt, Ideen und Verbindungen zu den Schriftrollen vom Toten Meer. Im Speziellen werden Themen in Bezug auf das aramäische Buch Tobit und 1 Henoch ausgearbeitet sowie die Verbindungen zwischen hebräischen Qumran-Apokryphen und den späteren apokalyptischen Schriften 4 Esra und 2 Baruch. Ein Kapitel über das Apokalyptische in Qumran führt einen neuen konzeptuellen Rahmen für das Thema ein. Gemeinsam bieten die Studien eine breitgefächerte und frische Perspektive auf die jüdische Literaturszene dieser Zeit, welche sich im Land Israel im letzten vor- und dem ersten nachchristlichen Jahrhundert entwickelte.
The volume assembles twenty previously published studies by Devorah Dimant, which have been re-edited, updated, and furnished with an introductory essay written especially for this collection. The studies survey and analyze Jewish works composed in Hebrew, Aramaic or Greek during the Second Temple period, and discuss their contents, ideas, and connections to the Dead Sea Scrolls. Particular attention is paid to central issues, such as the apocalyptic worldview and literature and its relationship to the Dead Sea Scrolls. Among others, specific themes related to the Aramaic Tobit and 1 Enoch are analyzed as well as the links detected between the Hebrew Qumran writings Pseudo-Ezekiel and the Apocryphon of Jeremiah and the later apocalyptic works 4 Ezra and 2 Baruch. The introductory essay provides a general framework and pertinent terminology for discussing the literature in question. Together these essays offer a broad and fresh perspective of the Jewish literary scene in antiquity, with special attention to the one nurtured in the land of Israel.
Keywords: Bibel; Apokryphen; Forschungen zum Alten Testament; Jüdische Literatur; Bildung (Paideia); Ressourcenknappheit; Religionskrieg; Hugo Grotius; Vertrauenshaftung; Apocryphal Acts of the Apostles; Forschungen zum Alten Testament; Alberico Gentili; Second Temple Literature; Ratifikation; Dead Sea Scrolls; Qumran; Apocalyptics; Apocryphal writings; Aramaic literature; Altes Testament; Neues Testament; Antike; Array; Aufsatzsammlung